Evaluation of the fulfillment of educational rights for children in conflict with the law through the filial school program - Ahmad Zulinto; Syukri Hamzah; Hadiwinarto Hadiwinarto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
The Palembang City Government through the Education Office in collaboration with the Regional Office of the Ministry of Law and Human Rights of South Sumatra Province as well as with other stakeholders initiated the implementation of Filial Schools Services for Child Prisoners at LPKA Class I Palembang. This study aimed at evaluating Filial Schools Filial Schools for Child Prisoners at LPKA Class I Palembang. This was evaluation research with a qualitative approach and using CIPP model. Data collection in this research was through observation, interviews, and documentation. The subjects of this study consisted of an accompanying teacher, a party from the Education Office, and a student. The data were analysed using Miles and Huberman model. The validity of the research data was obtained by using triangulation techniques by comparing the data from interviews, observations, and documentation. The study found that the fulfillment of educational right for children in conflict with the law through the Filial School Program at LPKA Class 1 Palembang has been going well. Based on the monitoring results, most of the children who have completed their education at LPKA have been able to improve their welfare. The Filial school program in providing the right to formal education for children through Quality Formal Education Services for Children at LPKA Class I Palembang has been going well. This program also presents the same curriculum as formal schools, also equipped with character building, as well as the development of various skills in students.